Modal Sosial di Kalangan Petani Rawa Pasang Surut (Studi Kasus: Desa Sumber Mulyo, Kabupaten Banyuasin) - Setianto, Suryawan (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2014)
The potential of swam di Indonesia is high leading to government intensively develope swam program within 3 years. Sumber Mulyo Village at Muara Telang district of Sumatera province has been chosen as one of swam development area. This research is aimed to find community social capital index Sumber Mulyo village which was transmigran from jawa island that is able to survive up to know. This research dealing the issue of lacking social capital consideration when developing swam. The method used is a qualitative descriptive approach supported by questionnaire instruments for data collection. This research shows that Sumber Mulyo village has a good social bounded. However, there is unexpected buyer that is strongly influencing post harvesting leading to minal sosial bridging dan linking. The process need to improve to keep the development of swam sustainable.